Factores que inciden en la infidelidad femenina en habitantes de la ciudad de Cali y el Distrito de Buenaventura - Benavides Castillo, Claudia Y. (Universidad Antonio Nariño, 2021)
The objective of this study was to determine the factors present in infidelity in a group of 20 women inhabitants of the city of Cali and 20 of the District of Buenaventura. Taking into account the review of the literature, it became evident that there is little research on the components that influence female infidelity. This scarcity could be attributed to the patriarchal models established socially and by family and/or cultural belief systems. That is why it was considered pertinent to address this research, in order to describe the factors that influence female infidelity, especially in 20 women inhabitants of the city of Cali and 20 of the District of Buenaventura, who had been in a relationship for at least one year. This research was conducted with the guidelines of the mixed type approach, with a descriptive scope and with the guidelines of the sequential explanatory design (DEXPLIS). The main findings were the following: the factor of dissatisfaction in the primary relationship, is the most relevant reason for being unfaithful in women from Cali with 70% and women from the District of Buenaventura with 40%. This in turn goes hand in hand with the stage of the interviews conducted, i.e. with the characterization of the subjective phenomena, where the four participants stated that they were unfaithful because of problems in the primary relationship, lack of attention from their partner, revenge and the search for satisfaction and sexual variety.